2010
DOI: 10.1212/wnl.0b013e3181c91873
|View full text |Cite
|
Sign up to set email alerts
|

Cancer linked to Alzheimer disease but not vascular dementia

Abstract: In white older adults, prevalent Alzheimer disease (AD) was longitudinally associated with a reduced risk of cancer, and a history of cancer was associated with a reduced risk of AD. Together with other work showing associations between cancer and Parkinson disease, these findings suggest the possibility that cancer is linked to neurodegeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
225
7
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(252 citation statements)
references
References 29 publications
17
225
7
3
Order By: Relevance
“…Recent evidence supports the observation of an inverse link between cancer and Alzheimer disease (13). The authors demonstrated that Alzheimer disease was longitudinally associated with a reduced risk of cancer, and a history of cancer was associated with a reduced risk of Alzheimer disease suggesting a common mechanism linking both diseases.…”
mentioning
confidence: 61%
“…Recent evidence supports the observation of an inverse link between cancer and Alzheimer disease (13). The authors demonstrated that Alzheimer disease was longitudinally associated with a reduced risk of cancer, and a history of cancer was associated with a reduced risk of Alzheimer disease suggesting a common mechanism linking both diseases.…”
mentioning
confidence: 61%
“…Increased risk of cancer seems to be associated with decreased chance of AD and there is a complex mechanism relating to these two diseases. These findings suggest the possibility that cancer can be linked to some neurodegenerative diseases (6). At the present time, the biological action of APP is not well explained in cancer cells.…”
Section: Discussionmentioning
confidence: 83%
“…High CHO intake, in particular in the form of sugar and other high GI foods, has been linked to modern diseases like metabolic syndrome [11], Alzheimer's disease [12,13], cataract and macula degeneration [14][15][16] and gout [17]. Intriguingly, with the possible exception of Alzheimer's disease [18], the occurrence and prognosis of cancer seems positively associated with both the prevalence of these diseases [19][20][21][22][23][24][25][26][27][28] and the GI and glycemic load (GL) of the diet [29][30][31][32]; this implies a possible role of high CHO intake in cancer as well.…”
Section: Modern Hunter-gatherers' Dietmentioning
confidence: 99%
“…This characteristic is the basis for the wide-spread use of the functional imaging modality positron emission tomography (PET) with the glucose-analogue tracer 18 F-fluoro-2-deoxyD-glucose (FDG) (Figure 1). There are mainly four possible drivers discussed in the literature that cause the metabolic switch from oxidative phosphorylation to aerobic glycolysis in cancer cells.…”
Section: Possible Causes For the "Warburg Effect"mentioning
confidence: 99%